2016
DOI: 10.3389/fnbot.2016.00015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating EMG Feature and Classifier Selection for Application to Partial-Hand Prosthesis Control

Abstract: Pattern recognition-based myoelectric control of upper-limb prostheses has the potential to restore control of multiple degrees of freedom. Though this control method has been extensively studied in individuals with higher-level amputations, few studies have investigated its effectiveness for individuals with partial-hand amputations. Most partial-hand amputees retain a functional wrist and the ability of pattern recognition-based methods to correctly classify hand motions from different wrist positions is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 36 publications
3
38
1
Order By: Relevance
“…The 10 steady-state segments for every gesture were concatenated and created a 10-s vector. We trained the classifier by extracting four timedomain features from the raw segmented data including mean absolute value, zero crossing, slope sign change, and waveform length (41). We chose for a feature extraction window of 200 ms (with an overlap of 100 ms), which would be within acceptable range for real-time myoelectric applications (42).…”
Section: Myocontrol Performancementioning
confidence: 99%
“…The 10 steady-state segments for every gesture were concatenated and created a 10-s vector. We trained the classifier by extracting four timedomain features from the raw segmented data including mean absolute value, zero crossing, slope sign change, and waveform length (41). We chose for a feature extraction window of 200 ms (with an overlap of 100 ms), which would be within acceptable range for real-time myoelectric applications (42).…”
Section: Myocontrol Performancementioning
confidence: 99%
“…Similarly, Ameri et al (2014) used an artificial neural network (ANN), where visual training was considered better than force training to simultaneously estimate intended movements of multiple joints. Comparing the classifiers performance, Adewuyi et al (2016) found for non-amputees and partial-hand amputees that LDA and ANN perform better than the quadratic discriminant analysis. Betthauser et al (2018) developed a robust sparsity-based adaptive classification method to get a classification system which is appreciably less sensitive to signal deviations between training and testing.…”
Section: Introductionmentioning
confidence: 99%
“…The classification accuracy under limb variation was improved by [11] with the selected subset out of 10 feature candidates. Adewuyi et al [12] evaluated the optimal sEMG feature subset in varying wrist positions for subjects with partial hand amputation and proved its superiority over the ensemble TD or TDAR features. Let alone the emphasis on the feature selection, the importance of the data segmentation with various window length of sEMG stream is addressed by [13].…”
Section: Introductionmentioning
confidence: 99%